2009
DOI: 10.1111/j.1476-5381.2009.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

The benzoxathiolone LYR‐71 down‐regulates interferon‐γ‐inducible pro‐inflammatory genes by uncoupling tyrosine phosphorylation of STAT‐1 in macrophages

Abstract: Background and purpose:Benzoxathiolone derivatives have shown anti-inflammatory and immunomodulatory potential in acne and psoriatic disorders. However, little is known about the molecular basis for these pharmacological effects. In this study, we decided to investigate the anti-inflammatory actions of a benzoxathiolone derivative LYR-71, 6-methyl-2-propylimino-6,7-dihydro-5H-benzo[1,3]oxathiol-4-one, in interferon (IFN)-g-activated macrophages. Experimental approach: RAW 264.7 macrophages or primary macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Deng et al performed RNA-seq on lesional skin from rosacea patients and found that the epidermal STAT1/IRF1 signature were observed in all rosacea subtypes 61 . STAT1-regulated gene transcription mediates many of the immune and inflammatory actions of IFN-γ 62 . Previous studies have implicated that IFN-γ is implicated in the pathogenesis of rosacea and acne.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al performed RNA-seq on lesional skin from rosacea patients and found that the epidermal STAT1/IRF1 signature were observed in all rosacea subtypes 61 . STAT1-regulated gene transcription mediates many of the immune and inflammatory actions of IFN-γ 62 . Previous studies have implicated that IFN-γ is implicated in the pathogenesis of rosacea and acne.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis and acne are common inflammatory skin diseases that involved in immune responses. Recent reports showed that an antiinflammatory effect of benzoxathiol derivatives was due to inhibition of NF-κB activation by targeting IKK as well as inhibition of STAT1 phosphorylation (Kim et al, 2008a(Kim et al, , 2008dChung et al, 2009). NF-κB is one of the transcription factors implicated in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, research by Chung et al. demonstrated the capacity of LYR-71, another benzoxathiolone, to inhibit IFN-γ-induced inflammatory responses, accomplished by uncoupling the tyrosine phosphorylation of STAT-1 in macrophages ( 80 ).…”
Section: Therapeutic Strategies and Potential Approaches Addressing M...mentioning
confidence: 99%